Determining factors in shaping the sustainable behavior of the generation Z consumer - Dragolea, Larisa-Loredana; Butnaru, Gina Ionela; Kot, Sebastian; Zamfir, Cristina Gabriela; Nuţă, Alina-Cristina; Nuţă, Florian-Marcel; Cristea, Dragoş Sebastian; Ştefănică, Mirela (Frontiers in Environmental Science, 2023)
Organizations currently emphasize green marketing strategies by implementing green marketing practices, aiming to design, produce, promote and sell green products. Thus, both consumers and producers have turned their attention to the category of green products, taking into account that the concept of green marketing is now being given greater importance. Based on the data collected through a survey (N = 787), we analyzed the sustainable behavior of Generation Z consumers studying at Romanian universities where there are specializations in this field. The research is quantitative, using structural equation modelling with partial least squares (PLS-SEM) to test the hypotheses regarding the relationship between the determining factors and the sustainable behavior of Generation Z consumers. The results show that there is a positive relationship between both the sustainable behavior of Generation Z consumers and the satisfaction it conveys to them, as well as their environmental protection activities, so that hypotheses H2, H5, H6 and H7 were validated. However, there is no relationship between the sustainable behavior of Generation Z consumers and the green marketing practices of the organizations, environmental issues and their identification with the green consumer, so the β coefficient values showed that the hypotheses H1, H3 and H4 were not validated. This study represents a contribution to the literature, since there have been no studies in the Romanian literature in this field, at least until now.